2019
DOI: 10.1002/pc.25451
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and water absorption of kenaf/pineapple leaf fiber‐reinforced polypropylene hybrid composites

Abstract: Hybrid composites have shown innumerable benefits to the research communities in terms of environmental friendliness and mechanical properties. This research study presents the mechanical characterization and moisture uptake of kenaf/pineapple leaf fiber‐reinforced polypropylene hybrid composites with several relative fiber ratios. A comparison was also made between nonhybrid and hybrid kenaf/pineapple leaf fiber‐reinforced composites to investigate the hybridization effect. In this work, the composite materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…where W 1 is the weight after immersion, W o is the initial weight, and W g is the weight gain percentage. Moreover, to measure the diffusion coefficient of moisture in the fabricated composite samples the Fick's law of diffusion is used [1,20] and the relation is given by Equation (11)…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…where W 1 is the weight after immersion, W o is the initial weight, and W g is the weight gain percentage. Moreover, to measure the diffusion coefficient of moisture in the fabricated composite samples the Fick's law of diffusion is used [1,20] and the relation is given by Equation (11)…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Moreover, to measure the diffusion coefficient of moisture in the fabricated composite samples the Fick's law of diffusion is used [ 1,20 ] and the relation is given by Equation ) D=πt4M20.25emM2M1t2t12, where D is the diffusion coefficient, t is the thickness, M ∞ is the saturation point moisture absorption percentage, 0.25emt2t1 is the linear portion‐time difference from the moisture absorption weight percentage curve, and M 2 – M 1 is a linear portion mass difference from the moisture absorption weight percentage curve.…”
Section: Materials and Experimental Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybridization of kenaf/pineapple was reported to increase the mechanical and water absorption resistance of polypropylene hybrid composites by N. L. Feng et al. [19] P. Madhu et al [20] and T. G. Y. Gowda et al [21] concluded that the evaluated mechanical properties were significantly increased for hybridization of Prosopis juliflora-glass-carbon and flax-basalt-carbon fiber reinforced polymer composites. Caryota urens natural fiber and glass fiber reinforced nanoclay/SiC toughened epoxy nanocomposite were reported to exhibit excellent mechanical and wear properties by P. Raju et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, PP has some limitations such as poor impact properties and non-biodegradability under environmental conditions. [12][13] In addition, blends of hydrophobic PP with hydrophilic natural fibers have a bad compatibility between matrix/fiber interfaces. [14] To solve these drawbacks, a number of approaches have been made, for example, impregnated with nanoparticles to improve the crystallization of polymer matrix, [15][16] mixing with natural fibers to be easily degraded, [17] and compatibility modified with coupling agents to increase the bonding between components.…”
Section: Introductionmentioning
confidence: 99%